2009
DOI: 10.1186/1743-0003-6-44
|View full text |Cite
|
Sign up to set email alerts
|

Performance adaptive training control strategy for recovering wrist movements in stroke patients: a preliminary, feasibility study

Abstract: BackgroundIn the last two decades robot training in neuromotor rehabilitation was mainly focused on shoulder-elbow movements. Few devices were designed and clinically tested for training coordinated movements of the wrist, which are crucial for achieving even the basic level of motor competence that is necessary for carrying out ADLs (activities of daily life). Moreover, most systems of robot therapy use point-to-point reaching movements which tend to emphasize the pathological tendency of stroke patients to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 23 publications
(26 reference statements)
1
39
0
1
Order By: Relevance
“…Because neuroplasticity is critical for recovery after a neurological injury, it has been suggested that the same mechanisms underlying motor learning may also contribute to motor recovery after injury [28], [29]. Although the concept of motor learning and its importance to motor recovery has been well studied in the upper extremity [30], [31], [32], [33], [34], this has been relatively overlooked in the lower extremity. This could be possibly due to the fact that walking is considered to be an automatic activity, essentially requiring little cognitive effort [35].…”
Section: Discussionmentioning
confidence: 99%
“…Because neuroplasticity is critical for recovery after a neurological injury, it has been suggested that the same mechanisms underlying motor learning may also contribute to motor recovery after injury [28], [29]. Although the concept of motor learning and its importance to motor recovery has been well studied in the upper extremity [30], [31], [32], [33], [34], this has been relatively overlooked in the lower extremity. This could be possibly due to the fact that walking is considered to be an automatic activity, essentially requiring little cognitive effort [35].…”
Section: Discussionmentioning
confidence: 99%
“…While these devices mainly target motor therapy at the shoulder and elbow joints, it has long been known that improvements observed at these joints do not generalize to wrist and hand [12]. To overcome this limitation, several wrist devices have been proposed in the last few years, including the MIT wrist robot [13], RiceWrist [14], HWARD [15], the Okayama University pneumatic manipulator [16], and the IIT wrist robot [17]. These robots can be used either as standalone therapy devices for wrist rehabilitation or coupled with other devices such as MIT-MANUS [18], ARMIN [19], HapticMaster [20], and wire-based device from [21] to deliver robot therapy to the whole upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…Masia et al [64] asked subjects to track a target moving in a sinusoidal pattern with wrist movement, and increased the required range of motion after each successful trial. Their preliminary results with three stroke subjects showed the potential of this method to increase subjects’ range of wrist motion.…”
Section: Toward Increased Patient Engagement In Therapymentioning
confidence: 99%